Study of floating bodies in wave ny using smoothed particle hydrodynamics (SPH) - Ha, Cheun Yuen, 1987-; Yeak, Su Hoe, 1971-; Fakulti Sains (2013)
Thesis (Sarjana Sains (Matematik Kejuruteraan)) - Universiti Teknologi Malaysia, 2013